Synthesis, Characterization and Antifungal Activity of Some Indolo [2-3-b] Quinoxaline Derivatives - Khitam Abdul Kareem Ismail (Journal of Global Pharma Technology, 2020)
In this research the focus was to synthesis new series of indolo [2-3-b] quinoxaline through the reaction of Isatin with 4-methyl-o-phenylenediamine in the presence of water to obtain 2-methyl-6H-indolo [2-3-b] quinoxaline (A1). Compound (A2) was prepared by refluxing  of compound (A1)  with chloroacetyl chloride in the presence of triethylamine, compound (A2)  was treated with hydrazine hydrate to give 2-hydrazino-1-(2-methyl-indolo[2,3-b]quinoxalin-6-yl)-ethanone (A3), While the Schiffe bases (A4- A8) were synthesized by the condensation of compounds (A3)  with aromatic aldehydes. The prepared compounds identified by spectral methods [FTIR, 1H-NMR] and measurement some of its physical properties. Furthermore we were studied the effects of the preparing compounds on some strains of Antifungal activity.Keywords: Isatin, Indolo [2-3-b] quinoxaline, Antifungal Activity, Schiffe base.